Chastity Beliefs, Female Neglect, Academic Achievement, and Psychological Well-Being of Adolescent Girls in Tamilnadu, India. Issue 3 (1st September 2016) - Mahalingam, Ramaswami; Balan, Sundari
Abstract : In this study, we examined the relationship between chastity beliefs and psychological well-being among adolescent girls with a specific focus on culturally valued beliefs about gender in communities with a history of extreme female neglect in Tamilnadu, India. We predicted that endorsing prescriptive gender norms would be positively related to resilience and lower levels of depressive symptoms and academic achievement. We found that, for adolescent girls ( N = 250), chastity beliefs were positively related to resilience ( b =.18, p <.01) and negatively related to depression ( b = -.24, p <.001) and academic performance ( b = -.40, p <.001). The ecological context of male-biased sex ratios shapes the lives of adolescent girls in complex ways. Although endorsing culturally valued gender beliefs enhanced the well-being of adolescent girls, it was also negatively correlated to their academic achievement. The cultural psychological implications of our findings for reproductive health education in India are discussed.